Isolation of Potential Antagonistic Rhizosphere Fungi against Alternaria alternata from Organic Carrot Productions - Noviyanti, Nita; Purwantisari, Susiana; Suprihadi, Agung (Universitas Gadjah Mada, 2024)
Rhizospheric fungi can have serve as biological agents against plant pathogens Alternaria alternata, which infects carrot plants. Rhizospheric fungi are more abundant in organic lands. This study aims to isolate fungi from organic carrot’s rhizosphere that are able to suppress A. alternata’s growth and determine isolate rhizospheric fungi ability to inhibit A. alternata to identify potential biological control agents against A. alternata. This research was conducted at the Laboratory of Biotechnology and Basic Biology, Diponegoro University, between January–June 2023. Research methods include survey location, soil sampling, rhizospheric fungi isolation, pathogenic fungi isolation, creating growth curve, pathogenicity tests, antagonism tests, and fungi identification. This study used a complete randomized design (CRD) and was analyzed using ANOVA at the 5% level of significance and Duncan's hoc-posttest. Fungi isolation from organic carrot plant’s rhizosphere resulted in 13 isolates consisting of six genera: Penicillium, Aspergillus, Paecilomyces, Myrothecium, Trichoderma, and Simplicillium. The antagonism test showed that eight antagonistic isolates, including the genus Penicillium (WO1, WO6, WO10), Paecilomyces (WO5), Myrothecium (WO7), Trichoderma (WO9), and Aspergillus (WO11, WO13), where WO1, WO6, WO10, and WO11 have a medium percentage of inhibition (44.12-57.84%), while WO5, WO7, WO9, and WO13 have a high percentage of inhibition (64.29-76.06%). The eight isolates showed antagonism mechanisms, including antibiosis (WO1, WO5, WO6, WO7, WO10, and WO11) and parasitism (WO9 and WO13).